Bahasa Inggris Penerapan Green Manajemen Sumber Daya Manusia Untuk Meningkatkan Daya Saing UMKM - Lenny Nawangsari; Nia Kusuma Wardhani (Jurnal Abdimas Perbanas, 2022)
Quality human resources and ,have global competitiveness are the determinants of the success of MSMEs. Green Human Resource Management (Green HRM) is one of the tools that can be used to manage the MSME workforce. Green human resource management is the management of human resources in a sustainable manner by paying attention to environmental aspects to preserve nature in the management of the company. The application of green HRM is one form of efforts to increase productivity and company commitment (MSMEs) in preserving the environment. The purpose of this community service activity is to provide knowledge to MSME actors about improving the quality of human resources through training and assistance involving stakeholders, namely local governments, entrepreneurs and academics to improve MSME competitiveness and implementing Green HRM strategies to improve MSME employee performance.